Strategic writing : multimedia writing for public relations, advertising, and more - Marsh, Charles; Guth, David W. ;Short, Bonnie Poovey (New York, NY : Routledge, 2018)
In its fourth edition, Strategic Writing emphasizes the goal-oriented mission of high-quality public relations and media writing with clear, concise instructions for more than 40 types of documents. This multidisciplinary text covers writing for public relations, advertising, sales and marketing, and business communication. In addition, it includes concise chapters on topics such as diversity, ethics and the legal aspects of strategic writing. Featuring a spiral binding, examples for each document and a user-friendly "recipe" approach, Strategic Writing is ideal for undergraduate PR or advertising writing classes that take an interdisciplinary approach. This new edition devotes new attention throughout to social media and writing in the digital realm, and features new and updated online resources for students and instructors.
Machine generated contents note: SECTION 1 Strategic Writing -- 1A.Introduction -- 1B.The Importance of Good Writing -- 1C.Research, Planning and the Writing Process -- 1D.Writing for the Web -- 1E.Writing for Social Media -- 1F.Broadcast/Podcast Writing -- 1G.Strategic Design -- 1H.Integrated Marketing Communications -- 1I.Ethics and Strategic Writing -- 1J.Diversity and Strategic Writing -- 1K.Persuasion and Strategic Writing -- 1L.The Law and Strategic Writing -- 1M.Jobs in Strategic Writing -- SECTION 2 Strategic Writing in Public Relations -- 2A.Introduction -- 2B.Social Media in Public Relations -- 2C.Microblogs and Status Updates -- 2D.Blogs -- 2E.Podcasts -- 2F.Websites -- 2G.News Release Guidelines -- 2H.Announcement News Releases -2I.Feature News Releases -- 2J.Hybrid News Releases -- 2K.Social Media News Releases -- 2L.Media Advisories -- 2M.Pitches -- 2N.Video News Releases and Organizational Storytelling -- 2O.Digital Newsrooms and Media Kits -- 2P.Backgrounders Note continued: 2Q.Fact Sheets -- 2R.Photo Opportunity Advisories -- 2S.Newsletter and Magazine Stories -- 2T.Annual Reports -- 2U.Speeches -- SECTION 3 Strategic Writing in Advertising -- 3A.Introduction -- 3B.Social Media in Advertising -- 3C.Strategic Message Planners -- 3D.Print Advertisements -- 3E.Radio Advertisements -- 3F.Television Advertisements -- 3G.Web and Mobile Advertisements -- 3H.Radio and TV Promotions -- 3I.Radio and TV Public Service Announcements -- SECTION 4 Strategic Writing in Sales and Marketing -- 4A.Introduction -- 4B.Social Media in Sales and Marketing -- 4C.Content Marketing -- 4D.Proposals and Marketing Communications Plans -- 4E.Mobile Messages -- 4F.Sales Letters and E-Blasts -- 4G.Fundraising Letters and E-Blasts -- 4H.Brochures -- SECTION 5 Strategic Writing in Business Communication -- 5A.Introduction -- 5B.Social Media in Business Communication -- 5C.Business Correspondence -- 5D.Good-News Correspondence Note continued: 5E.Bad-News Correspondence -- 5F.Request Correspondence -- 5G.Job-Request Correspondence -- 5H.Resumes -- 5I.Memoranda -- 5J.Business Reports -- Appendices -- A.A Concise Guide to Punctuation -- B.A Concise Guide to Grammar -- C.A Concise Guide to Style -- DTips for Oral Presentations
Includes index.
Keywords: BUSINESS WRITING